Occurrence of Anaplasma and Ehrlichia species in African buffalo (Syncerus caffer) in Kruger National Park and Hluhluwe-iMfolozi Park in South Africa - Collins, Nicola E. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.